The Determination of Product Distribution Route based on Nearest Neighbour and Genetic Algorithm - Y Erdhianto; Suhartini Suhartini; Sutrisno Sutrisno; R Mitrasari (Institut Teknologi Sepuluh Nopember, 2018)
One of logistics activities is product distribution. PT Stars has several obstacles in their distribution activity including the limited number and capacity of the company vehicles, the difference in the number of consumer requests, and the spread consumer locations. The methods used in this research were Saving Matrix, Nearest Neighbor, and Genetic Algorithm. By employing biological evolution concept, an output was produced in the form of a combination of goods distribution route that should be taken to optimize the capacity and travel cost. The results obtained from the calculation on Saving Matrix and Nearest Neighbor were two routes for Genetic Algorithm manually and constructively using MATLAB at PT Stars Internasional. Based on the calculation process, two solutions were obtained using Nearest Neighbor with two distribution routes, while 14 distribution routes were generated using Genetic Algorithm with a maximum capacity of 3,720 pairs.